2008
DOI: 10.1186/1477-7819-6-32
|View full text |Cite
|
Sign up to set email alerts
|

Merkel cell carcinoma of the upper extremity: Case report and an update

Abstract: Background: Merkel cell carcinoma is a rare but aggressive cutaneous primary small cell carcinoma. It is commonly seen in elderly affecting the head, neck, and extremities. Macroscopically may be difficult to distinguish MCC from other small cells neoplasms especially oat cell carcinoma of the lung.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
16

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 39 publications
(59 reference statements)
0
15
0
16
Order By: Relevance
“…[4] MCC most commonly occurs in the head and neck (50%), upper and lower limbs (35-40%), and less than 10% in the trunk. [5] Similarly, our patient also had MCC in the head and neck region. The epidemiological studies have revealed that large tumor size, male sex, truncal site, nodal/distant disease at presentation, and duration of disease before presentation are poor prognostic factors.…”
Section: Discussionmentioning
confidence: 85%
“…[4] MCC most commonly occurs in the head and neck (50%), upper and lower limbs (35-40%), and less than 10% in the trunk. [5] Similarly, our patient also had MCC in the head and neck region. The epidemiological studies have revealed that large tumor size, male sex, truncal site, nodal/distant disease at presentation, and duration of disease before presentation are poor prognostic factors.…”
Section: Discussionmentioning
confidence: 85%
“…It has very rarely been described on the fingers or the hand, with only few case reports that we are aware of [3][4][5][6][7][8][9][10][11][12][13][14][15]16]. Because of its rarity and the small numbers of patients in clinical reports, management is not standardized.…”
Section: Discussionmentioning
confidence: 97%
“…Adjuvant radiation therapy has been clearly proven to provide benefit in local regional recurrence rate [3,5]. However, distant metastases and overall survival seem to be similar compared to those who did not receive radiation therapy [14]. Chemotherapy is recommended in case of distant metastases.…”
Section: Discussionmentioning
confidence: 99%
“…For an MCC metastatic disease (Stage III), radio- and chemotherapy are employed with a palliative intent [23]. MCC is predominantly a radio-sensitive malignancy, and utilization of radiation therapy is highly advised [24].…”
Section: Discussionmentioning
confidence: 99%